THE USE OF MODERN INNOVATIVE TECHNOLOGIES IN TEACHING ENGLISH - Aziza, Pulatova (INTEGRATION OF SCIENCE, EDUCATION AND PRACTICE. SCIENTIFIC-METHODICAL JOURNAL, 2022)
This article covers the great importance given to foreign languages in the Republic of Uzbekistan, as well as the innovative technologies necessary for their study.